MiR‐216a promotes breast cancer cell apoptosis by targeting PKCα. (31st May 2019) - Cui, Ying; Wang, Jinghao; Liu, Shanshan; Qu, Di; Jin, Hong; Zhu, Lin; Yang, Jiani; Zhang, Jingchun; Li, Qingwei; Zhang, Yanqiao; Yao, Yuanfei
Abstract: Breast cancer (BC) is the most common cause of death in women throughout the world. MicroRNAs (miRNAs, miR) have been identified as key regulators in carcinogenesis of several cancers, including BC. MicroRNA‐216a (miR‐216a) is downregulated in several cancers. Here, we evaluated the effects of miRNA‐216a on breast cancer cells and the underlying mechanisms. miR‐216a level was quantified by real‐time RT‐PCR. Cell viability was analyzed by MTT assay. Wound‐healing assay was performed for detection of cell migration. Apoptosis was detected by TUNEL and caspase‐3 activity assay. Moreover, the level of protein expression was determined by Western blot. We found that miR‐216a expression was remarkably decreased in both human BC tissues and MCF‐7 cells. miR‐216a overexpression dramatically suppressed the migration and promoted the apoptosis in cultured MCF‐7 cells. We validated PKCα (protein kinase C alpha, PRKCA) as a direct target of miR‐216a. Knockdown of PKCα induced apoptosis and inhibited migration in cultured MCF‐7 cells which were reversed by miR‐216a inhibitor. Moreover, the level of miR‐216a is negatively correlated with PKCα in cell lines. Our results collectively suggest that miR‐216a suppressed migration and promoted apoptosis in breast cancer cells by targeting PKCα. These findings indicate that manipulation of miR‐216a expression may represent a novel therapeutic strategy in the treatment of breast cancer.